On The Homogeneous Third Degree Diophantine Equation With Four Unknowns (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The homogeneous third degree equation with four unknowns represented by the Diophantine equation                              =is considered for its patterns of non – zero integral solutions. A few fascinating properties among the solutions and special integer are presented.